(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2012)
LearningCounts.org was established in 2010 by the Council for Adult and Experiential Learning (CAEL) to expand the availability of prior learning assessment (PLA) services across the United States. The services offered by LearningCounts.org can contribute to improved institutional completion rates and provide additional support for institutions looking to expand PLA offerings at their campuses. What follows is a fuller description of this project – it’s goals, services and benefits.